2021
DOI: 10.48550/arxiv.2102.11284
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A composite solution to the EDGES anomaly

Anubhav Mathur,
Surjeet Rajendran,
Harikrishnan Ramani

Abstract: Subcomponent millicharged dark matter that cools baryons via Coulomb interactions has been invoked to explain the EDGES anomaly. However, this model is in severe tension with constraints from cosmology and stellar emissions. In this work, we consider the consequences of these millicharged particles existing in composite blobs. The relevant degrees of freedom at high temperature are minuscule elementary charges, which fuse at low temperatures to make up blobs of larger charge. These blobs serve as the degrees o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Since we, nonetheless, recover ρ b /ρ γ = ρ b /ρ γ , this difference does not affect any CMB observables, but can play an important role in hidden sector BBN. While hidden BBN does not affect visible sector CMB observables, it may have interesting observational consequences that warrant further study [32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 95%
“…Since we, nonetheless, recover ρ b /ρ γ = ρ b /ρ γ , this difference does not affect any CMB observables, but can play an important role in hidden sector BBN. While hidden BBN does not affect visible sector CMB observables, it may have interesting observational consequences that warrant further study [32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 95%
“…MCP models have recently been explored in detail as potential explanations of the anomalously small spin temperature of the hydrogen atoms measured by the EDGES experiment [22,[24][25][26][27]. This anomaly can be resolved if the baryons were cooled by scattering with DM particles.…”
Section: Millicharged Particle Modelmentioning
confidence: 99%
“…This anomalously large depth has received considerable attention in the literature. Many studies explain the depth either by postulating excess cooling of cosmic hydrogen due to novel physical mechanisms (Barkana 2018;Muñoz & Loeb 2018;Berlin et al 2018;Houston et al 2018;Li et al 2021;Mathur et al 2021), or by bringing into play a part of the excess radio background observed at relevant frequencies (Feng & Holder 2018;Pospelov et al 2018;Moroi et al 2018;Sierra & Fong 2018;Fraser et al 2018;Ewall-Wice et al 2018;Jana et al 2018;Chianese et al 2019;Lawson & Zhitnitsky 2019;Choi et al 2020;. Some studies invoke even more exotic scenarios, such as a modified Hubble parameter at cosmic dawn (Hill & Baxter 2018;Costa et al 2018;Wang & Zhao 2018;Xiao et al 2019), new coupling terms in the spin temperature (Widmark 2019;Lambiase & Mohanty 2020;Dhuria et al 2021), or special classes of dark energy and dark matter models (Mukhopadhyay et al 2021).…”
Section: Introductionmentioning
confidence: 99%